Into the woods ebook - Harrison, Kim (The Hollows, 2012)
A true queen of urban fantasy—the New York Times bestselling author of the wildly popular series featuring bounty hunter witch-turned-daywalking demon Rachel Morgan—the phenomenal Kim Harrison explores the Hollows more deeply than ever before in Into the Woods, her first collection of short stories. Rachel is here, as are Jenks the pixie, elven tycoon Trent Kalamack, and an unholy host of vampires, demons, shapeshifters, ghosts, and other assorted supernatural beings, friends and foes. Into the Woods combines original work, including a new Hollows novella, as well as all of Kim Harrison's previously published short fiction gathered together in one volume for the very first time. No true Hollows aficionado will want to pass this up—and readers of Laurell K. Hamilton, Kelley Armstrong, Patricia Briggs, and Jim Butcher; fans of Stephanie Meyer's Twilight novels and of paranormal romance superstars Christine Feehan and Sherrilyn Kenyon, will be likewise enchanted.